Cultural Determinants and Moral Imperatives in the Socialization of the Individual - Muydinjonovich, Abrorjon Ismatov (Indonesian Journal Publisher, 2025)
The article analyzes the role of cultural determinants and moral imperatives in the process of individual socialization based on philosophical and sociological approaches. Socialization is considered not only as a result of economic and political factors but also as a process shaped by a system of cultural values, traditions, and customs. Special attention is paid to moral imperatives as a methodological basis for an individual’s assimilation of social norms, spiritual principles, and ethical values. The study examines the significance of cultural determinants in social adaptation, identity formation, and moral stability of the individual, as well as the transformation of these factors in the context of globalization. The article contributes to a deeper understanding of socialization mechanisms in modern society and the development of theoretical and practical frameworks for preserving national values.